Student information retrieval using Geographical Information System - Roziyah, Abdul Razak (2006)
An effective and faster data retrieval technique is important when dealing among systems with large database. The existing Hostel Management System in Students Affairs Department (HEP) of University College of Engineering and Technology Malaysia (KUKTEM) involves thousands of student data.As a result,the processing time of data retrieval becoming lengthy.This system also restricted the administrator to detect student's location visually.In order to solve these flaws,Student Information Retrieval using Geographical Information System (GIS) is developed.This system focused on discovering student information based on their student identification number and name by applying geographical location/map concept.This new system provide functions zoom in,zoom out,panning,identify and query builder in order to simplify the data manipulation by the administrator.By applying the data visualization technique using GIS the administrator can retrieve data faster and in an interactive way.